Influence of physical object’s qualities on perception of form by touch - Lapė, J. (Psichologija, 1962)
This work presents experiment data regarding the influence of physical object qualities on perception of form by touching. The data received by the experiment show that reflection of special qualities of an object is affected by skin deformation which occurs during the interaction of surface receptors and the object. These skin deformation changes are incurred by different physical qualities of an object (smoothness, roughness, elasticity).